Reinterpretasi Sakralitas Sape’ Karaang pada Ritual Hudo’ Dayak Bahau di Kota Samarinda - Syahputra, Yudi; Putra, Bayu Arsiadhi; Setyoko, Aris (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
The Dayak Bahau community in Samarinda City has experienced changes in their cultural system, in this case their religious elements are no longer adherents of animist beliefs. However, they still believe in the legacy of their ancestors' animist beliefs, namely Sape' Karaang as a sacred musical instrument practiced in the Hudo' ritual. Thus, this research aims to analyze how the belief in the sacredness and practice of Sape' Karaang can survive amid changes in the religious system of the Dayak Bahau community in Samarinda City. This research uses qualitative methods with observation, data collection and data analysis techniques. Data collection techniques include literature study, interviews, and documentation. Data found in the field were collected and then analyzed. The results showed that the reason for the survival of the belief in the sacredness of Sape' Karaang in the Dayak Bahau community in Samarinda City is due to the reinterpretation by their traditional leaders of past animist sacred sources. Furthermore, the results of this interpretation form a new perception in the Dayak Bahau community of the sacredness of Sape' Karaang. For this reason, Sape' Karaang is still believed to be sacred and practiced by the Dayak Bahau community, which in turn has implications for their cultural identity in Samarinda City.